2005
DOI: 10.1177/0269881105048899
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of depression: time to consider folic acid and vitamin B12

Abstract: We review the findings in major depression of a low plasma and particularly red cell folate, but also of low vitamin B12 status. Both low folate and low vitamin B12 status have been found in studies of depressive patients, and an association between depression and low levels of the two vitamins is found in studies of the general population. Low plasma or serum folate has also been found in patients with recurrent mood disorders treated by lithium. A link between depression and low folate has similarly been fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
195
1
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(226 citation statements)
references
References 60 publications
2
195
1
12
Order By: Relevance
“…Folate is metabolized into S-adenosylmethionine (SAMe) and both are involved in the production of dopamine, norepinephrine and serotonin, all neurotransmitters implicated in depression. These neurotransmitters affect the production of tertrahydrobiopterin, an antioxidant and cofactor in the synthesis of these neurotransmitters [9,10].…”
Section: Editorialmentioning
confidence: 99%
“…Folate is metabolized into S-adenosylmethionine (SAMe) and both are involved in the production of dopamine, norepinephrine and serotonin, all neurotransmitters implicated in depression. These neurotransmitters affect the production of tertrahydrobiopterin, an antioxidant and cofactor in the synthesis of these neurotransmitters [9,10].…”
Section: Editorialmentioning
confidence: 99%
“…Its beneficial effects on the function of this system is associated with its participation in the formation of neuro-stimulating substances in the body such as dopamine, norepinephrine and epinephrine (Paul et al 2004, Coppen & Bolander-Gouaille 2005, Reynolds 2006). Many clinical and epidemiological studies have shown that folate deficiency in the diet leads to a number of neuropsychiatric disorders such as depression, psychosis, dementia and seizures (Quadri et al 2004, Luchsinger et al 2007.…”
Section: Importance Of Folates For the Human Nutritionmentioning
confidence: 99%
“…Low levels of folate have been implicated in poor response rates to standard antidepressant therapy. 26 B vitamins also convert glucose into energy in the brain cells and assists in the manufacture of neurotransmitters. B 12 is essential for nerve cell health.…”
Section: Replacing Missing Nutrientsmentioning
confidence: 99%